Análisis de la vulnerabilidad sísmica del edificio de la EMAPA-G cantón Guaranda. período noviembre 2022 - febrero 2023. - Chimborazo Cisneros, Diego Geovanny (2023)
Seismic events are unpredictable, their ability to affect buildings depends on the intensity with which they occur and the conditions of the buildings, however, their destructive nature affects buildings slightly, partially, totally and even in some cases leads to their collapse. With the passing of the years and the experiences on the levels of affectation of the earthquakes in the territories, methodologies have been incorporated to evaluate the behavior of the buildings against seismic events, for this reason the purpose of the investigation is to model the behavior of the EMAPA-G building against seismic events, using the Cypecad methodology. It was obtained as a result that the building has a high level of vulnerability, in addition to vibration T with a factor Z= 0.35 a Ta= 0.41 with a percentage of 30% was estimated, in addition to a displacement percentage in module 1 of 11.58% in addition to the value LGZ= 0.998, this due to the architectural configuration of the building and in the drifts with R=8 resulted in values less than 1/50, which means that the building is within the values allowed in the NEC. Keywords: Collapse, Destructive, Intensity, Modeling, Seismic